2020
DOI: 10.3390/pathogens9030185
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Screening of 239 Traditional Chinese Medicinal Plant Extracts for Their Antibacterial Activities against Multidrug-Resistant Staphylococcus aureus and Cytotoxic Activities

Abstract: Novel alternative antibacterial compounds have been persistently explored from plants as natural sources to overcome antibiotic resistance leading to serious foodborne bacterial illnesses. In this study, the ethanolic extracts from 239 traditional Chinese medicinal plants (TCMP)’ materials were screened to discover promising candidates that have strong antibacterial properties against multidrug-resistant Staphylococcus (S.) aureus and low cytotoxicity. The results revealed that 74 extracts exhibited good antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 81 publications
(110 reference statements)
4
25
0
Order By: Relevance
“…Several studies reported that allicin could inhibit MDR bacterial growth such as S. aureus , E. coli , MRSA, and P. aeruginosa ; however, this effect is bacteriostatic, which suggested using allicin in combination with other antibiotics [ 175 , 176 ]. As a mechanism, allicin inhibits bacterial enzymes like alcohol dehydrogenase, RNA polymerase, DNA gyrase, as well as inhibition of biofilm formation, DNA, and protein synthesis [ 175 , 177 ]. Allicin presence in garlic was first reported by Cavallito and Bailey in 1944 [ 178 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that allicin could inhibit MDR bacterial growth such as S. aureus , E. coli , MRSA, and P. aeruginosa ; however, this effect is bacteriostatic, which suggested using allicin in combination with other antibiotics [ 175 , 176 ]. As a mechanism, allicin inhibits bacterial enzymes like alcohol dehydrogenase, RNA polymerase, DNA gyrase, as well as inhibition of biofilm formation, DNA, and protein synthesis [ 175 , 177 ]. Allicin presence in garlic was first reported by Cavallito and Bailey in 1944 [ 178 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Allicin presence in garlic was first reported by Cavallito and Bailey in 1944 [ 178 ]. It is a chemically unstable compound that rapidly decomposes to sulfide compounds such as ajoenes, diallyl sulfide (DAS), and diallyl disulfide (DADS) [ 175 ]. Thus, five analogues of allicin had been synthesized to overcome the stability problem [ 179 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Chu, is a flowering plant of family Rosaceae. XHC exhibits anti-inflammatory, anti-oxidant and antimicrobial activities (Kim et al, 2017;Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from the various parts show activity against clinical pathogenic bacteria such as Bacillus cereus, B. subtilis, Escherichia coli, Klebsiella pneumonia, Proteus sps., Pseudomonas aeruginosa, Shigella dysentriae, S. flexneri, S. sonnei, Staphylococcus aureus, S. intermedius, Streptococcus suis and Vibrio cholera (Ali et al 1998;Uddin et al 2003;Das and Choudhury 2010;Radhika et al 2011;Moirangthem et al 2013;Fan et al 2015;Panda et al 2016;Sithisarn et al 2016Sithisarn et al , 2019SatyaEswari et al 2018;Kim et al 2020), fungal species including Aspergillus fumigates, Candida albicans, and Macrofomina phaeolina (Ali et al 1998;Moirangthem et al 2013), the worm Hymenolepis diminuta (Deori and Yadav 2016), and Chikungunya virus (Mohamat et al 2018).…”
Section: Bioactivitymentioning
confidence: 99%